2018
DOI: 10.1007/s00234-018-2050-0
|View full text |Cite
|
Sign up to set email alerts
|

Normal development of sacrococcygeal centrum ossification centers in the fetal spine: a postmortem magnetic resonance imaging study

Abstract: We have presented the timing of appearance of individual sacrococcygeal COCs and the age-specific, normative MRI reference values for sacral length and the morphometric parameters of the sacral COCs, which are of clinical importance in the diagnosis of congenital sacral abnormalities and skeletal dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…We assumed that the negative results in that study were derived from the small age range. Other studies on foetal MRI have shown that sacral length, height, and sagittal and transverse diameters increase linearly with advancing gestational age [ 18 , 19 ]. Nevertheless, even in our study, for infants younger than one year, although the correlation coefficients were all >0.7, the R-squared values of simple regressions were less than 0.7 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that the negative results in that study were derived from the small age range. Other studies on foetal MRI have shown that sacral length, height, and sagittal and transverse diameters increase linearly with advancing gestational age [ 18 , 19 ]. Nevertheless, even in our study, for infants younger than one year, although the correlation coefficients were all >0.7, the R-squared values of simple regressions were less than 0.7 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The spine should be examined in all three planes. Hypomineralisation of the vertebral bodies is a very useful aid to the diagnosis of achondrogenesis (Figures B,D), but the sonographer should be wary of over diagnosing this as ossification of the cervical and sacral vertebral bodies occurs later in pregnancy up to 28 weeks' gestation . The spine may appear to be disorganised secondary to hemivertebrae, which may or may not be associated with rib anomalies in conditions such as VATER and Jarcot Levine, but the ectopic calcification seen in some chondrodysplasia punctatas also results in a disorganised appearance (Figures C,D).…”
Section: The Sonographic Approach To the Diagnosis Of Generalised Skementioning
confidence: 99%
“…Over the past several years, magnetic resonance imaging (MRI) has been used increasingly as an adjunct examination to US for the evaluation of fetal anomalies (9,10) and has proven useful in imaging fetal spinal canals and cord pathologies (11) with ultrafast spinecho T2-weighted imaging sequences (12)(13)(14)(15)(16)(17). However, literature regarding the use of MRI for the diagnosis of the musculoskeletal system (18)(19)(20)(21) and, in particular, bony spinal structures, is scarce and mainly focuses on postmortem imaging examinations without vertebral developmental abnormalities (22)(23)(24)(25)(26) or case reports (27,28). Recently, with the improvement and modification of fetal imaging of the susceptibility-weighted imaging (SWI) sequence, the application of fetal MRI for bony spinal structures has attracted mounting attention (29,30).…”
Section: Introductionmentioning
confidence: 99%